Method for loading catalyst through ion implantation, prepared catalyst and application
By implanting metal ion on the current collector surface of the current collector or loading carrier material, a catalyst is prepared, which solves the problems of high overpotential and high load of precious metals in the existing electrolytic water hydrogen production technology, and achieves efficient and economical hydrogen production.
Patent Information
- Application Number
- CN202411583005.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-07
AI Technical Summary
In the existing electrolytic water hydrogen production technology, the cathode and anode have high overpotentials, resulting in low electrolytic efficiency, high energy consumption, and high loading of precious metals, limiting the large-scale application of catalysts.
The catalyst is prepared by performing metal ion implantation on the current collector surface of the current collector or the loading carrier material, thereby achieving excellent catalytic performance under low precious metal loads.
This method increases the specific surface area of the catalyst under a lower catalyst loading capacity, reduces the overpotential, and improves the efficiency and economicality of electrolyzed hydrogen production. It is suitable for large-scale production and industrial applications of catalysts.
Smart Images

Figure CN119530856A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical hydrogen production, and in particular relates to a method for loading a catalyst by ion implantation, a prepared catalyst and an application thereof. Background Art
[0002] The global demand for energy is increasing, and the environmental problems caused by the burning of fossil energy are becoming increasingly serious. The development of renewable clean energy is urgent. Hydrogen has the advantages of high energy density (143MJ / kg) and zero carbon emissions when burned, and is considered to be the best substitute for traditional fossil energy. At present, the use of renewable energy such as solar energy and wind energy to electrolyze water to produce hydrogen is an effective means to convert renewable energy into green hydrogen energy. The electrolysis of water to produce hydrogen has the advantages of near-zero emissions and high product purity (up to 99.9%). It is the most promising clean hydrogen production technology and is considered to be an effective solution to the energy crisis and environmental pollution problems. However, since the hydrogen evolution reaction at the cathode and the oxygen evolution reaction at the anode in the process of electrolysis of water to produce hydrogen involve complex multiple proton coupling and multi-electron transfer processes, higher cathode and anode polarization overpotentials are required, resulting in the actual operating voltage of commercial electrolyzers being much higher than the theoretical value (1.23V), low electrolysis efficiency, high energy consumption, and not economical for large-scale hydrogen production. How to improve energy conversion efficiency and reduce power consumption has become a "bottleneck" problem that needs to be solved urgently. Electrocatalysts are the key to reducing overpotential and improving energy conversion efficiency. By selecting suitable electrocatalysts, the kinetics of various reactions can be regulated and the overpotential can be reduced. Currently, the most effective catalysts for oxygen evolution and hydrogen evolution reactions are Ir / Ru-based catalysts and Pt-based catalysts, respectively. At present, there are mainly the following methods for loading catalysts on current collectors: impregnation-liquid phase reduction method, colloidal method, electrochemical method or vapor deposition method. However, the catalysts prepared by existing methods have a high loading of precious metals, small reserves of precious metals, and high prices, which limits the large-scale application of catalysts.
[0003] Therefore, how to make the catalyst have excellent catalytic performance at a lower noble metal loading or when using non-noble transition metals has become a difficult problem in the prior art. Summary of the invention
[0004] The purpose of the present invention is to provide a method for loading catalyst by ion implantation, a catalyst prepared by the method provided by the present invention and its application. The catalyst prepared by the method provided by the present invention still has excellent catalytic performance when the metal loading is low.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for ion implantation to load a catalyst, comprising the following steps:
[0007] Metal ion implantation is performed on the surface of the current collector to obtain a catalyst;
[0008] Alternatively: (1) mixing a carrier material with a solvent and a binder to obtain a mixed slurry; the carrier material comprises at least one of graphene, metal chalcogenide, carbon nanotube and graphyne;
[0009] (2) coating the mixed slurry obtained in step (1) onto a current collector to obtain a current collector loaded with a carrier material;
[0010] (3) Metal ion implantation is performed on the surface of the current collector of the carrier material obtained in step (2) to obtain a catalyst.
[0011] Preferably, in step (1), the ratio of the mass of the carrier material, the volume of the solvent and the volume of the binder is 1 mg: (180-220) μL: (10-20) μL.
[0012] Preferably, in the step (2), the ratio of the mass of the carrier material in the current collector loaded with the carrier material to the surface area of the current collector is (0.5-1.5) mg: 1 cm 2 .
[0013] Preferably, the current collector in step (2) comprises one of carbon paper, carbon cloth, copper foam and nickel foam.
[0014] Preferably, the metal ions in step (3) include at least one of iron ions, cobalt ions, nickel ions, copper ions, gold ions, molybdenum ions, platinum ions, ruthenium ions, aluminum ions, niobium ions, rhodium ions, iridium ions, palladium ions, silver ions, titanium ions, zinc ions, chromium ions and manganese ions.
[0015] Preferably, the metal ion implantation dose in step (3) is 1×10 15 ~5×10 17 ions·cm -2 .
[0016] Preferably, the energy of the low-energy ion beam during metal ion implantation in step (3) is 5 to 100 keV.
[0017] Preferably, the metal ion implantation in step (3) is performed under vacuum conditions.
[0018] The present invention also provides a catalyst prepared by the method for ion implantation and catalyst loading described in the above technical solution.
[0019] The present invention also provides the use of the catalyst described in the above technical solution in the production of hydrogen by electrolysis of water.
[0020] The present invention provides a method for loading a catalyst by ion implantation, comprising the following steps: implanting metal ions on the surface of a current collector to obtain a catalyst; or: (1) mixing a carrier material with a solvent and a binder to obtain a mixed slurry; the carrier material comprises at least one of graphene, metal sulfide compounds, carbon nanotubes and graphyne; (2) coating the mixed slurry obtained in the step (1) on a current collector to obtain a current collector loaded with a carrier material; (3) implanting metal ions on the surface of the current collector loaded with a carrier material obtained in the step (2) to obtain a catalyst. The present invention implants metal ions on the surface of a current collector or a current collector loaded with a carrier material, which brings two different effects, including an energy effect and a mass effect. The energy effect refers to the fact that metal ion implantation introduces defect sites on the current collector or the carrier material, assisting catalysis or assisting in anchoring the implanted ions; the mass effect refers to the introduction of catalyst atoms on the current collector or the carrier material by metal ion implantation, and the loaded catalyst exists in the form of single atoms or a few atom clusters. The method can increase the specific surface area of the catalyst while reducing the catalyst loading amount, thereby reducing the overpotential and improving the catalytic performance. At the same time, this method is a universal catalyst loading method. Due to the uniformity of ion implantation, the uniformity of catalyst loading can be achieved. At the same time, large-scale batch production of catalysts can be achieved, which is conducive to industrial application. The scale of the catalyst depends on the structure of the implanter. The results of the embodiment show that the catalyst prepared by the present invention can reach an overpotential that can only be achieved by 20wt% commercial Pt / C when its loading amount is 5wt%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of a process for preparing a catalyst using the method of the present invention and for electrochemically decomposing water;
[0022] Figure 2 LSV curves of the electrochemical water decomposition and hydrogen evolution reaction of the catalyst prepared in Example 1 of the present invention and commercial Pt / C;
[0023] Figure 3 The Tafel curves of the catalyst prepared in Example 1 of the present invention and the commercial Pt / C electrochemical water decomposition hydrogen evolution reaction;
[0024] Figure 4 The EIS curves of the electrochemical water decomposition and hydrogen evolution reaction of the catalyst prepared in Example 1 of the present invention and commercial Pt / C;
[0025] Figure 5 The catalyst prepared in Example 1 of the present invention and the commercial Pt / C electrochemical water decomposition hydrogen evolution reaction C dl curve;
[0026] Figure 6X-ray photoelectron spectroscopy (XPS) of the catalyst prepared in Example 1 of the present invention;
[0027] Figure 7 For Figure 6 The figure after decomposition of the Pt peak in the X-ray photoelectron spectrum;
[0028] Figure 8 The L3 edge X-ray absorption near edge structure spectrum (XANES) of Pt in the catalyst prepared in Example 1 of the present invention;
[0029] Fig. 9 For Figure 8 Perform a transformation graph of R space;
[0030] Fig.10 For the general Figure 8 Wavelet transform graph of ;
[0031] Fig.11 This is a spherical aberration corrected high-resolution transmission electron microscopy image of the catalyst prepared in Example 1 of the present invention;
[0032] Fig.12 This is an element EDS mapping diagram of the catalyst prepared in Example 1 of the present invention;
[0033] Fig.13 LSV curves of the electrochemical water decomposition and hydrogen evolution reaction of the catalysts prepared in Examples 2 to 4 of the present invention;
[0034] Fig.14 The Tafel curve diagram of the electrochemical water decomposition and hydrogen evolution reaction of the catalyst prepared in Examples 2 to 4 of the present invention;
[0035] Fig.15 The LSV curve of the electrochemical water decomposition and hydrogen evolution reaction of the catalyst prepared in Examples 1 and 2 of the present invention;
[0036] Fig.16 The Tafel curve of the electrochemical water decomposition and hydrogen evolution reaction of the catalyst prepared in Examples 1 and 2 of the present invention;
[0037] Fig.17 LSV curves of the electrochemical water decomposition and hydrogen evolution reaction of the catalysts prepared in Examples 5 to 6 of the present invention;
[0038] Fig.18 The Tafel curve of the electrochemical water decomposition and hydrogen evolution reaction of the catalyst prepared in Examples 5 to 6 of the present invention;
[0039] Fig.19 The EIS curves of the electrochemical water decomposition and hydrogen evolution reaction of the catalysts prepared in Examples 5 to 6 of the present invention;
[0040] Fig. 20The catalyst prepared in Examples 5 to 6 of the present invention is used for the electrochemical decomposition of water and hydrogen evolution reaction. dl curve;
[0041] Fig.21 LSV curves of the electrochemical water decomposition and oxygen evolution reaction of the catalysts prepared in Examples 7 to 9 of the present invention;
[0042] Fig. 22 The Tafel curves of the electrochemical water decomposition and oxygen evolution reaction of the catalysts prepared in Examples 7 to 9 of the present invention;
[0043] Fig.23 The EIS curves of the electrochemical water decomposition and oxygen evolution reaction of the catalysts prepared in Examples 7 to 9 of the present invention;
[0044] Fig.24 The catalyst prepared in Examples 7 to 9 of the present invention is used for electrochemical water decomposition and oxygen evolution reaction. dl curve;
[0045] Fig.25 A target plate is used to place a current collector in the process chamber of an ion implanter for ion implantation. DETAILED DESCRIPTION
[0046] The present invention provides a method for ion implantation to load a catalyst, comprising the following steps:
[0047] Metal ion implantation is performed on the surface of the current collector to obtain a catalyst;
[0048] Alternatively: (1) mixing a carrier material with a solvent and a binder to obtain a mixed slurry; the carrier material comprises at least one of graphene, metal chalcogenide, carbon nanotube and graphyne;
[0049] (2) coating the mixed slurry obtained in step (1) onto a current collector to obtain a current collector loaded with a carrier material;
[0050] (3) Metal ion implantation is performed on the surface of the current collector of the carrier material obtained in step (2) to obtain a catalyst.
[0051] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.
[0052] The invention provides a method for loading catalyst by ion implantation, comprising the following steps: implanting metal ions on the surface of a current collector to obtain a catalyst.
[0053] In the present invention, the current collector preferably includes one of carbon paper, carbon cloth, foam copper and foam nickel.
[0054] In the present invention, the metal ions preferably include at least one of iron ions, cobalt ions, nickel ions, copper ions, gold ions, molybdenum ions, platinum ions, ruthenium ions, aluminum ions, niobium ions, rhodium ions, iridium ions, palladium ions, silver ions, titanium ions, zinc ions, chromium ions and manganese ions. In the present invention, the metal ions are used as catalysts.
[0055] In the present invention, the implantation dose of the metal ions is preferably 1×10 15 ~5×10 17 ions·cm -2 , more preferably 3×10 16 ~2.5×10 17 ions·cm -2 .
[0056] In the present invention, the metal ion implantation method is preferably: injecting a low-energy ion beam into the surface of the current collector under vacuum conditions.
[0057] In the present invention, the pressure of the vacuum condition is preferably 5×10 -3 ~5×10 -4 Pa, more preferably 2×10 -3 ~5×10 -4 Pa.
[0058] In the present invention, the energy of the low-energy ion beam during the metal ion implantation is preferably 5 to 100 keV, more preferably 10 to 50 keV, and further preferably 10 to 30 keV.
[0059] The present invention limits the implantation dosage of metal ions and the energy of the low-energy ion beam within the above range, so that the implanted metal can be a single atom or a few-atom clusters, further improving the catalytic performance.
[0060] In the present invention, the metal ion implantation is preferably completed in an ion implanter. The present invention has no special limitation on the model of the ion implanter, and an ion implanter well known to those skilled in the art can be used. In the present invention, the metal target in the ion implanter preferably includes at least one of an iron target, a cobalt target, a nickel target, a copper target, a gold target, a molybdenum target, a platinum target, a ruthenium target, an aluminum target, a niobium target, a rhodium target, an iridium target, a palladium target, a silver target, a titanium target, a zinc target, a chromium target and a manganese target. In the present invention, the ion source of the ion implanter directly generates plasma from a solid material through a metal vapor vacuum arc discharge, and then extracts the metal ions through an extractor and a mass selector, and obtains an ion beam with a high current density through acceleration.
[0061] The present invention also provides a method for ion implantation to load a catalyst, comprising the following steps:
[0062] (1) mixing a carrier material with a solvent and a binder to obtain a mixed slurry;
[0063] (2) coating the mixed slurry obtained in step (1) onto a current collector to obtain a current collector loaded with a two-dimensional material;
[0064] (3) Metal ion implantation is performed on the surface of the current collector loaded with the two-dimensional material obtained in step (2) to obtain a catalyst.
[0065] The present invention mixes the carrier material with the solvent and the binder to obtain a mixed slurry.
[0066] In the present invention, the carrier material includes at least one of graphene, metal sulfide, carbon nanotube and graphyne. In the present invention, the carrier material enables subsequent metal ions to be uniformly loaded, further improving the performance of the catalyst. In the present invention, the metal sulfide preferably includes molybdenum disulfide; the sheet diameter of the molybdenum disulfide is preferably 0.2-5 μm; the thickness of the molybdenum disulfide is preferably 1-8 nm; the carbon nanotube is preferably a multi-walled carbon nanotube; the purity of the multi-walled carbon nanotube is preferably> 95%, the length is preferably 0.5-2 μm, and the diameter is preferably <8 nm; the graphene is preferably reagent grade, the thickness is preferably 1-3 nm, the number of layers is preferably <3, and the diameter is preferably> 50 μm. In an embodiment of the present invention, the graphene, molybdenum disulfide and carbon nanotube are all purchased from Pioneer Nano. In the present invention, the length of the graphyne is preferably 250 nm and the thickness is preferably 2.35 nm. The present invention has no special limitation on the source of the graphyne, and products prepared by conventional commercial products or conventional preparation methods can be used.
[0067] In the present invention, the solvent preferably includes at least one of isopropanol, anhydrous ethanol and deionized water, and isopropanol is more preferred; the purity of the isopropanol is preferably >99.7%.
[0068] In the present invention, the binder preferably includes at least one of Nafion solution, polyvinylidene fluoride (PVDF) and polyvinyl alcohol (PVA), and more preferably Nafion solution.
[0069] In the present invention, the mass concentration of the Nafion solution is preferably 4-6%, more preferably 5%.
[0070] In the present invention, the mass of the carrier material, the volume of the solvent and the volume ratio of the binder are preferably 1 mg: (180-220) μL: (10-20) μL, more preferably 1 mg: 185 μL: 15 μL. The present invention limits the mass of the carrier material, the volume of the solvent and the volume ratio of the binder to the above range, so that the carrier material can be fully dispersed and can be better coated and bonded to the current collector later.
[0071] The present invention has no special limitation on the operation of mixing the carrier material with the solvent and the binder, and the raw materials can be fully dispersed by using a material mixing technical scheme well known to those skilled in the art. In an embodiment of the present invention, the mixing is ultrasonic; the ultrasonic time is 1 hour; the ultrasonic temperature is room temperature; and the ultrasonic power is 1200W.
[0072] After obtaining the mixed slurry, the present invention applies the mixed slurry to a current collector to obtain a current collector loaded with a carrier material.
[0073] In the present invention, the current collector preferably includes one of carbon paper, carbon cloth, copper foam and nickel foam. The present invention has no special limitation on the sources of carbon paper, carbon cloth, copper foam and nickel foam, and commercial products known to those skilled in the art can be used. In an embodiment of the present invention, the carbon paper is from Suzhou Shengernuo Technology Co., Ltd., brand Toray; the thickness of the nickel foam is 1.6 mm, and the surface density is 350 g / m 2 .
[0074] In the present invention, the current collector is preferably pretreated before use.
[0075] In the present invention, the pretreatment preferably includes cutting, washing and drying performed in sequence.
[0076] The present invention has no special limitation on the size of the current collector after cutting, and it can be selected according to actual needs. In an embodiment of the present invention, the size of the current collector after cutting is 1*1cm 2 .
[0077] In the present invention, the washing preferably comprises ultrasonic treatment using acetone, ethanol and deionized water in sequence.
[0078] The present invention has no particular limitation on the amount of acetone, ethanol and deionized water used, as long as they can cover the current collector.
[0079] The present invention has no special limitation on the ultrasonic parameters, as long as the oil and impurities on the surface of the current collector are removed. In an embodiment of the present invention, the ultrasonic treatment time is 30 minutes; the ultrasonic treatment temperature is room temperature; and the ultrasonic treatment power is 1200W.
[0080] In the present invention, the washing is used to remove oil stains and impurities on the surface of the current collector.
[0081] In the present invention, the drying is preferably vacuum drying; the vacuum degree of the vacuum drying is preferably 0.01Pa to 1Pa, more preferably 0.1Pa; the temperature of the vacuum drying is preferably 60 to 80°C, more preferably 70°C; the time of the vacuum drying is preferably 8 to 12h, more preferably 10h.
[0082] In the present invention, the ratio of the mass of the carrier material in the current collector loaded with the carrier material to the surface area of the current collector is preferably (0.5-1.5) mg:1 cm 2 , more preferably 1mg:1cm 2 The present invention limits the ratio of the mass of the carrier material in the current collector loaded with the carrier material to the surface area of the current collector within the above range, which is more conducive to the subsequent loading of metal ions on the carrier and more conducive to the performance comparison with catalysts loaded in other ways.
[0083] The present invention has no special limitation on the coating operation, and a coating technical solution well known to those skilled in the art is adopted to ensure that the mass ratio of the carrier material in the current collector loaded with the carrier material after coating to the volume ratio of the current collector is within the above range. In an embodiment of the present invention, the coating is performed by drop coating with a pipette gun.
[0084] After coating, the present invention preferably dries the coated product to obtain a current collector loaded with the carrier material.
[0085] In the present invention, the drying is preferably vacuum drying; the vacuum degree of the vacuum drying is preferably 0.01Pa to 1Pa, more preferably 0.1Pa; the temperature of the vacuum drying is preferably 60 to 80°C, more preferably 70°C; the time of the vacuum drying is preferably 8 to 12h, more preferably 10h.
[0086] After obtaining the current collector of the carrier material, the present invention performs metal ion implantation on the surface of the current collector of the carrier material to obtain a catalyst.
[0087] In the present invention, the metal ions preferably include at least one of iron ions, cobalt ions, nickel ions, copper ions, gold ions, molybdenum ions, platinum ions, ruthenium ions, aluminum ions, niobium ions, rhodium ions, iridium ions, palladium ions, silver ions, titanium ions, zinc ions, chromium ions and manganese ions. In the present invention, the metal ions are used as catalysts.
[0088] In the present invention, the implantation dose of the metal ions is preferably 1×10 15 ~5×10 17 ions·cm -2 , more preferably 3×10 16 ~2.5×10 17 ions·cm -2 .
[0089] In the present invention, the metal ion implantation method is preferably: injecting a low-energy ion beam into the surface of the current collector of the carrier material under vacuum conditions.
[0090] In the present invention, the pressure of the vacuum condition is preferably 5×10 -3 ~5×10 -4 Pa, more preferably 2×10 -3 ~5×10 -4 Pa.
[0091] In the present invention, the energy of the low-energy ion beam during the metal ion implantation is preferably 5 to 100 keV, more preferably 10 to 50 keV, and further preferably 10 to 30 keV.
[0092] The present invention limits the implantation dosage of metal ions and the energy of the low-energy ion beam within the above range, so that the implanted metal can be a single atom or a few-atom clusters, further improving the catalytic performance.
[0093] In the present invention, the metal ion implantation is preferably completed in an ion implanter. The present invention has no special limitation on the model of the ion implanter, and an ion implanter well known to those skilled in the art can be used. In the present invention, the metal target in the ion implanter preferably includes at least one of an iron target, a cobalt target, a nickel target, a copper target, a gold target, a molybdenum target, a platinum target, a ruthenium target, an aluminum target, a niobium target, a rhodium target, an iridium target, a palladium target, a silver target, a titanium target, a zinc target, a chromium target and a manganese target. In the present invention, the ion source of the ion implanter directly generates plasma from a solid material through a metal vapor vacuum arc discharge, and then extracts the metal ions through an extractor and a mass selector, and obtains an ion beam with a high current density through acceleration.
[0094] In the present invention, the target source of the ion implanter excites and induces metal ions, and when the metal ions are loaded onto a carrier, they are called catalyst atoms. This is because in the current field of electrocatalysis, single-atom catalysis is a new concept that has been proposed, specifically referring to the monodisperse state of the catalyst on the carrier. Because the catalyst is adsorbed on the carrier, there will be more or less charge transfer and charge interaction, presenting metallic bonds and / or covalent bonds, rather than an independent existence state, and even the catalyst atoms will interact with each other to form small atom clusters.
[0095] The schematic diagram of the process for preparing the catalyst and using it for electrochemical water decomposition by the method of the present invention is preferably as follows Figure 1 As shown. Figure 1 As can be seen in the figure, the carrier material is coated on the current collector, and then metal ions are implanted on the surface of the carrier material to obtain a catalyst, which can be used for electrochemical water decomposition.
[0096] The present invention performs metal ion implantation on the surface of a current collector or a current collector loaded with a carrier material, which brings about two different effects, including an energy effect and a mass effect. The energy effect refers to the fact that metal ion implantation will introduce defect sites on the current collector or the carrier to assist in catalysis or to assist in anchoring the injected ions; the mass effect refers to the introduction of catalyst atoms on the current collector or the carrier by metal ion implantation. The metal ions are implanted onto the surface of the current collector or the carrier. During the electrocatalytic decomposition of water, the metal ions continuously adsorb and desorb reaction intermediates to promote charge transport and transfer, thereby effectively reducing the overpotential of the redox reaction of electrolytic water, controlling the preparation process so that the loaded catalyst is a single atom or a few-atom cluster, providing a larger specific surface area to reduce the overpotential and improve the catalytic performance under the premise of a smaller catalyst loading amount.
[0097] The present invention also provides a catalyst prepared by the method for ion implantation and catalyst loading described in the above technical solution.
[0098] The catalyst prepared by the invention still has excellent catalytic performance when the metal ion loading amount is low.
[0099] The present invention also provides the use of the catalyst described in the above technical solution in the production of hydrogen by electrolysis of water.
[0100] The present invention has no special limitation on the operation of the application, and the technical solutions of the application well known to those skilled in the art may be adopted.
[0101] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0102] Example 1
[0103] A method for ion implantation loading catalyst: (1) molybdenum disulfide (sheet diameter of 0.2 to 5 μm, thickness of 1 to 8 nm, Pioneer Nano), isopropanol and 5% Nafion solution are ultrasonically treated at room temperature and 1200 W power for 1 h to obtain a mixed slurry in a ratio of 1 mg: 185 μL: 15 μL;
[0104] (2) Cut the carbon paper (Suzhou Shengernuo Technology Co., Ltd., brand Toray) into 1*1cm 2, acetone, ethanol and deionized water were used for ultrasonic treatment at room temperature and 1200 W power for 30 minutes respectively, and vacuum dried at 0.1 Pa and 70°C for 10 hours, and then the mixed slurry obtained in step (1) was dripped onto the surface of the cleaned and dried carbon paper using a pipette gun, and vacuum dried at 0.1 Pa and 70°C for 10 hours to obtain carbon paper loaded with molybdenum disulfide, wherein the mass of molybdenum disulfide and the surface area of carbon paper The ratio is 1 mg: 1 cm 2 ;
[0105] (3) In an ion implanter, the target material of the ion implanter is a platinum target material. Platinum ions are implanted on the surface of the carbon paper loaded with molybdenum disulfide in step (2). -3 Pa vacuum conditions, a low-energy ion beam was implanted into the surface of carbon paper loaded with MoS2, and the implantation dose of platinum ions was 2.5×10 17 ions·cm -2 The energy of the low-energy ion beam is 20 keV, and the catalyst obtained is recorded as MoS2-5.0Pt.
[0106] Example 2
[0107] A method for ion implantation to load a catalyst: (1) graphene (reagent grade, thickness of 1 to 3 nm, number of layers <3, diameter of 50 to 100 μm, Pioneer Nano), isopropanol and a 5% mass concentration Nafion solution are ultrasonically treated at room temperature and 1200 W power for 1 h to obtain a mixed slurry;
[0108] (2) Cut the carbon paper (Suzhou Shengernuo Technology Co., Ltd., brand Toray) into 1*1cm 2 , acetone, ethanol and deionized water were used for ultrasonic treatment at room temperature and 1200 W power for 30 minutes respectively, and vacuum dried at 0.1 Pa and 70°C for 10 hours, and then the mixed slurry obtained in step (1) was dripped onto the surface of the cleaned and dried carbon paper using a pipette gun, and vacuum dried at 0.1 Pa and 70°C for 10 hours to obtain graphene-loaded carbon paper, wherein the mass of graphene and the surface area of carbon paper are 1 mg: 1 cm 2 ;
[0109] (3) In an ion implanter, platinum ions are implanted on the surface of the carbon paper loaded with graphene in step (2) at 1×10 -3 Pa vacuum conditions, low-energy ion beams were implanted into the surface of graphene-loaded carbon paper, with an implantation dose of 2.5×10 17 ions·cm -2 The energy of the low-energy ion beam is 20 keV, and the catalyst obtained is recorded as 1 mgGr-5.0Pt.
[0110] Example 3
[0111] A method for ion implantation loading catalyst: (1) molybdenum disulfide (sheet diameter of 0.2 to 5 μm, thickness of 1 to 8 nm, Pioneer Nano), isopropanol and 5% Nafion solution are ultrasonically treated at room temperature and 1200 W power for 1 h to obtain a mixed slurry in a ratio of 1 mg: 185 μL: 15 μL;
[0112] (2) Cut the carbon paper (Suzhou Shengernuo Technology Co., Ltd., brand Toray) into 1*1cm 2 , acetone, ethanol and deionized water were used for ultrasonic treatment at room temperature and 1200 W power for 30 minutes respectively, and vacuum dried at 0.1 Pa and 70°C for 10 hours, and then the mixed slurry obtained in step (1) was dripped onto the surface of the cleaned and dried carbon paper using a pipette gun, and vacuum dried at 0.1 Pa and 70°C for 10 hours to obtain carbon paper loaded with molybdenum disulfide, wherein the mass of molybdenum disulfide and the surface area of carbon paper The ratio is 1 mg: 1 cm 2 ;
[0113] (3) In an ion implanter, iron ions are implanted on the surface of the carbon paper loaded with molybdenum disulfide in step (2) at 1×10 -3 Pa vacuum conditions, low-energy ion beams were implanted into the surface of carbon paper loaded with MoS2, and the implantation dose of iron ions was 2.5×10 17 ions·cm -2 The energy of the low-energy ion beam is 20 keV, and the catalyst obtained is recorded as 1 mgMoS2-5.0Fe.
[0114] Example 4
[0115] A method for ion implantation to load a catalyst: (1) carbon nanotubes (multi-walled carbon nanotubes, purity > 95%, length 0.5-2 μm, diameter < 8 nm, Pioneer Nano), isopropanol and 5% mass concentration Nafion solution are ultrasonically treated at room temperature and 1200 W power for 1 h to obtain a mixed slurry;
[0116] (2) Cut the carbon paper (Suzhou Shengernuo Technology Co., Ltd., brand Toray) into 1*1cm 2 , acetone, ethanol and deionized water were used for ultrasonic treatment at room temperature and 1200 W power for 30 minutes respectively, and vacuum dried at 0.1 Pa and 70°C for 10 hours, and then the mixed slurry obtained in step (1) was drop-coated on the surface of the cleaned and dried carbon paper with a pipette gun, and vacuum dried at 0.1 Pa and 70°C for 10 hours to obtain carbon paper loaded with carbon nanotubes, wherein the mass of carbon nanotubes and the surface area of carbon paper are 1 mg: 1 cm 2 ;
[0117] (3) In an ion implanter, nickel ions are implanted on the surface of the carbon paper loaded with carbon nanotubes in step (2) at 1×10 -3 Pa vacuum conditions, low energy ion beams were implanted into the surface of carbon paper loaded with carbon nanotubes. The implantation dose of nickel ions was 3×10 16 ions·cm -2 The energy of the low-energy ion beam is 20 keV, and the catalyst obtained is recorded as 1 mgCNT-3E16Ni.
[0118] Example 5
[0119] A method for ion implantation to load a catalyst: (1) carbon nanotubes (multi-walled carbon nanotubes, purity > 95%, length 0.5-2 μm, diameter < 8 nm, Pioneer Nano), isopropanol and 5% mass concentration Nafion solution are ultrasonically treated at room temperature and 1200 W power for 1 h to obtain a mixed slurry;
[0120] (2) Nickel foam (thickness 1.6 mm, surface density 350 g / m 2 )Cut into 1*1cm 2 , acetone, ethanol and deionized water were used for ultrasonic treatment at room temperature and 1200 W power for 30 minutes respectively, and vacuum dried at 0.1 Pa and 70°C for 10 hours, and then the mixed slurry obtained in step (1) was drop-coated on the surface of the cleaned and dried nickel foam by a pipette gun, and vacuum dried at 0.1 Pa and 70°C for 10 hours to obtain a nickel foam loaded with carbon nanotubes, wherein the mass of the carbon nanotubes and the surface area of the nickel foam were 1 mg: 1 cm 2 ;
[0121] (3) In an ion implanter, platinum ions are implanted on the surface of the nickel foam loaded with carbon nanotubes in step (2) at 1×10 -3 Pa vacuum conditions, low-energy ion beams were implanted into the surface of nickel foam loaded with carbon nanotubes. The implantation dose of platinum ions was 3×10 16 ions·cm -2 The energy of the low-energy ion beam is 20 keV, and the catalyst is obtained, which is recorded as NF-1mgCNT-3E16Pt.
[0122] Example 6
[0123] A method for ion implantation to load a catalyst: (1) carbon nanotubes (multi-walled carbon nanotubes, purity > 95%, length 0.5-2 μm, diameter < 8 nm, Pioneer Nano), isopropanol and 5% mass concentration Nafion solution are ultrasonically treated at room temperature and 1200 W power for 1 h to obtain a mixed slurry;
[0124] (2) Nickel foam (thickness 1.6 mm, surface density 350 g / m 2 )Cut into 1*1cm 2 , acetone, ethanol and deionized water were used for ultrasonic treatment at room temperature and 1200 W power for 30 minutes respectively, and vacuum dried at 0.1 Pa and 70°C for 10 hours, and then the mixed slurry obtained in step (1) was drop-coated on the surface of the cleaned and dried nickel foam by a pipette gun, and vacuum dried at 0.1 Pa and 70°C for 10 hours to obtain a nickel foam loaded with carbon nanotubes, wherein the mass of the carbon nanotubes and the surface area of the nickel foam were 1 mg: 1 cm 2 ;
[0125] (3) In an ion implanter, molybdenum ions are implanted on the surface of the nickel foam loaded with carbon nanotubes in step (2) at 1×10 -3 Pa vacuum conditions, low-energy ion beams were implanted into the surface of nickel foam loaded with carbon nanotubes. The implantation dose of molybdenum ions was 3×10 16 ions·cm -2 The energy of the low-energy ion beam is 20 keV, and the catalyst is obtained, which is recorded as NF-1mgCNT-3E16Mo.
[0126] Example 7
[0127] A method for ion implantation to load a catalyst: (1) carbon nanotubes (multi-walled carbon nanotubes, purity > 95%, length 0.5-2 μm, diameter < 8 nm, Pioneer Nano), isopropanol and 5% mass concentration Nafion solution are ultrasonically treated at room temperature and 1200 W power for 1 h to obtain a mixed slurry;
[0128] (2) Nickel foam (thickness 1.6 mm, surface density 350 g / m 2 )Cut into 1*1cm 2 , acetone, ethanol and deionized water were used for ultrasonic treatment at room temperature and 1200 W power for 30 minutes respectively, and vacuum dried at 0.1 Pa and 70°C for 10 hours, and then the mixed slurry obtained in step (1) was drop-coated on the surface of the cleaned and dried nickel foam by a pipette gun, and vacuum dried at 0.1 Pa and 70°C for 10 hours to obtain a nickel foam loaded with carbon nanotubes, wherein the mass of the carbon nanotubes and the surface area of the nickel foam were 1 mg: 1 cm 2 ;
[0129] (3) In an ion implanter, iron ions are implanted on the surface of the nickel foam loaded with carbon nanotubes in step (2) at 1×10 -3Pa vacuum conditions, low-energy ion beams were implanted into the surface of nickel foam loaded with carbon nanotubes. The implantation dose of iron ions was 1×10 17 ions·cm -2 The energy of the low-energy ion beam is 20 keV, and the catalyst is obtained, which is recorded as NF-1mgCNT-1E17Fe.
[0130] Example 8
[0131] A method for ion implantation to load a catalyst: (1) carbon nanotubes (multi-walled carbon nanotubes, purity > 95%, length 0.5-2 μm, diameter < 8 nm, Pioneer Nano), isopropanol and 5% mass concentration Nafion solution are ultrasonically treated at room temperature and 1200 W power for 1 h to obtain a mixed slurry;
[0132] (2) Nickel foam (thickness 1.6 mm, surface density 350 g / m 2 )Cut into 1*1cm 2 , acetone, ethanol and deionized water were used for ultrasonic treatment at room temperature and 1200 W power for 30 minutes respectively, and vacuum dried at 0.1 Pa and 70°C for 10 hours, and then the mixed slurry obtained in step (1) was drop-coated on the surface of the cleaned and dried nickel foam by a pipette gun, and vacuum dried at 0.1 Pa and 70°C for 10 hours to obtain a nickel foam loaded with carbon nanotubes, wherein the mass of the carbon nanotubes and the surface area of the nickel foam were 1 mg: 1 cm 2 ;
[0133] (3) In an ion implanter, cobalt ions are implanted on the surface of the nickel foam loaded with carbon nanotubes in step (2) at 1×10 -3 Pa vacuum conditions, low-energy ion beams were implanted into the surface of nickel foam loaded with carbon nanotubes. The implantation dose of cobalt ions was 1×10 17 ions·cm -2 The energy of the low-energy ion beam is 20 keV, and the catalyst is obtained, which is recorded as NF-1mgCNT-1E17Co.
[0134] Example 9
[0135] A method for ion implantation to load a catalyst: (1) carbon nanotubes (multi-walled carbon nanotubes, purity > 95%, length 0.5-2 μm, diameter < 8 nm, Pioneer Nano), isopropanol and 5% mass concentration Nafion solution are ultrasonically treated at room temperature and 1200 W power for 1 h to obtain a mixed slurry;
[0136] (2) Nickel foam (thickness 1.6 mm, surface density 350 g / m 2)Cut into 1*1cm 2 , acetone, ethanol and deionized water were used for ultrasonic treatment at room temperature and 1200 W power for 30 minutes respectively, and vacuum dried at 0.1 Pa and 70°C for 10 hours, and then the mixed slurry obtained in step (1) was drop-coated on the surface of the cleaned and dried nickel foam by a pipette gun, and vacuum dried at 0.1 Pa and 70°C for 10 hours to obtain a nickel foam loaded with carbon nanotubes, wherein the mass of the carbon nanotubes and the surface area of the nickel foam were 1 mg: 1 cm 2 ;
[0137] (3) In an ion implanter, iron ions are implanted on the surface of the nickel foam loaded with carbon nanotubes in step (2) at 1×10 -3 Pa vacuum conditions, low-energy ion beams were implanted into the surface of nickel foam loaded with carbon nanotubes. The implantation dose of iron ions was 2.5×10 17 ions·cm -2 The energy of the low-energy ion beam is 20 keV, and the catalyst is obtained, which is recorded as NF-1mgCNT-2.5E17Fe.
[0138] Application Examples
[0139] The catalysts prepared in Examples 1 to 9 and commercial Pt / C were used for electrochemical water decomposition to produce hydrogen using a three-electrode system, wherein the catalysts prepared in Examples 1 to 9 and commercial Pt / C were working electrodes, the counter electrode was a platinum sheet electrode, and the reference electrode was Ag / AgCl immersed in a saturated KCl solution, the electrolyte was 1 mol / L KOH, and the LSV and CV measurements were performed in the potential range of -0.9 to 0.2 V relative to the standard hydrogen electrode, with scan rates of 5 and 100 mV / s, respectively. The AC impedance measurement was performed in the same configuration, 10 mA / cm 2 The potential was from 10 -1 Up to 10 5 hertz.
[0140] The catalysts prepared in Examples 1 to 9 and commercial Pt / C were used to carry out the reduction reaction of water electrolysis and hydrogen evolution reaction. The CV (cyclic voltammetry), LSV (linear voltammetry), EIS (electrochemical impedance spectroscopy), C dl Double layer capacitance, and the fitted Tafel slope, etc., where CV is a full activation of the sample, and LSV is the overpotential when a certain current value is provided, usually 10mA·cm -2The overpotential value at the time of electrolysis is used for comparison. In the actual electrolytic cell reaction process, the actual cathode potential is lower than the theoretical potential and the actual anode potential is higher than the theoretical potential. The voltage values below and above are called overpotentials, and the loss comes from electrochemical polarization and concentration difference polarization. The Tafel slope is usually fitted by the LSV curve and is used to describe the relationship between potential and current density. The value of the Tafel slope represents the change in potential when the current increases or decreases by 10 times. The smaller the value, the faster the reaction kinetics of OER or HER in electrolysis of water and the better the catalytic activity. EIS characterizes the impedance characteristics of various aspects of the catalyst through the relationship between the change of AC impedance and frequency. The internal resistance (R s ) and charge transfer resistance (R ct ), so as to analyze the electrochemical performance of the catalyst. The intercept between the front end of the semicircle and the X-axis represents R s , which can be used to perform IR correction on the polarization curve to compensate for the voltage loss caused by the internal resistance of the solution. The radius of the semicircle represents R ct , the smaller the value, the stronger the electron transport ability of the catalyst and the faster the kinetic process; the electrochemical active area is the effective area involved in the electrochemical reaction. Usually, electrode reactions include Faraday processes and non-Faraday processes. The Faraday process is a process in which a redox reaction occurs on the electrode and is accompanied by charge transfer between the electrode and the solution interface. In the non-Faraday process, no redox reaction occurs. It is due to the adsorption or desorption process and the charging and discharging of the double layer at the interface between the electrode and the solution, which causes current to flow. The study of electrochemical active area (ECSA) is based on the electrochemical double layer capacitance (C dl ) principle, ECSA and C dl is proportional to the C dl Taking the open circuit voltage of the electrolytic cell system as the center and 0.1V as the voltage window, cyclic voltammetry (CV) tests were performed at different scan rates to fit a straight line between the scan rate and the current density. The slope of the straight line is C dl .
[0141] LSV, Tafel, EIS and C of the prepared catalyst and commercial Pt / C catalyst for electrochemical water decomposition and hydrogen evolution reaction dl The curves are Figures 2 to 5 As shown. The catalyst prepared in Example 1 was tested by inductively coupled plasma emission spectrometer (ICP) and the Pt content of the commercial Pt / C catalyst was 20wt%. Figures 2 to 5 It can be seen that the dose of platinum ion implantation is 2.5×10 17 ions·cm-2 The catalytic performance is better than that of commercial Pt / C, reflecting its lower overpotential, which represents its excellent catalytic performance. -1 ) is lower than commercial Pt / C (47.24mV dec -1 ), reflecting its faster reaction kinetics. The radius of the EIS impedance spectrum is smaller than that of commercial Pt / C, reflecting its faster charge transfer kinetics. dl The value (249.95mF / cm 2 ) is greater than commercial Pt / C (235.6mF / cm 2 ), reflecting its larger electrochemical active area.
[0142] The X-ray photoelectron spectroscopy (XPS) of the catalyst prepared in Example 1 is as follows: Figure 6 As shown, Figure 6 The peak of Pt in the X-ray photoelectron spectrum is shown in the figure after decomposition. Figure 7 As shown. Figures 6-7 It can be seen from the content and valence of Pt that there is almost no 0-valent Pt, and the content of 2-valent Pt is very high. Pt may be related to S 2- After bonding, it presents +2 valence.
[0143] The L3 edge X-ray absorption near edge structure spectrum (XANES) of Pt in the catalyst prepared in Example 1 is as follows: Figure 8 As shown, through Figure 8 The peak before the middle edge indicates that the valence state of the platinum single atom (Pt-SA) is between 0 and 4. Figure 8 Perform an R space transformation to obtain Fig. 9 . Fig. 9 The structural fitting shows that the Pt in the intermediate valence state between 0 and 4 exists in the form of Pt-S bond. 2 There is no obvious Pt-Pt bond in the R space transformation, which further illustrates the single atomic form of Pt. Figure 8 The wavelet transform of Fig.10 shown. Fig.10 While displaying the coordination bond length, the types of coordinated atoms can be intuitively displayed. Figures 8 to 10 It can be seen that after injecting Pt with MoS2 as the carrier, no obvious Pt-Pt bond is seen in the synchrotron radiation spectrum, but obvious Pt-S bond can be observed, indicating that the average existence form of the catalyst is in the form of single atom or few-atom clusters, which has a larger specific surface area and thus has higher catalytic activity.
[0144] The spherical aberration corrected high-resolution transmission electron microscopy image of the catalyst prepared in Example 1 is as follows: Fig.11As shown, through Fig.11 The atomic brightness can be seen in the single atom form of Pt. The element EDS mapping diagram of the catalyst prepared in Example 1 is as follows: Fig.12 As shown. Fig.12 It can be seen that the Pt, S and Mo elements are evenly distributed in the catalyst.
[0145] The LSV and Tafel curves of the electrochemical water decomposition and hydrogen evolution reaction of the catalysts prepared in Examples 2 to 4 are shown as follows: Figures 13-14 As shown. Figures 13-14 It can be seen that ion implantation is a universal method for loading electrocatalytic catalyst metal ions. Different carriers and implanted ions can be selected and arranged in various ways. The values of Tafel slopes are: Example 2 (1 mg Gr-5.0 Pt) is 100.43 mV dec -1 , Example 3 (1 mgMoS2-5.0Fe) is 105.17 mV dec -1 , Example 3 (1 mg CNT-3E16Ni) is 390.02 mV dec -1 , the catalyst with the best catalytic performance is still the one injected with Pt.
[0146] The LSV and Tafel curves of the electrochemical water decomposition and hydrogen evolution reaction of the catalysts prepared in Examples 1 and 2 are shown as follows: Figures 15-16 As shown. Figures 15-16 It can be seen that the values of Tafel slope are: Example 1 (1 mgMoS2-5.0Pt) is 46.85 mV dec -1 , Example 2 (1 mg Gr-5.0 Pt) is 100.43 mV dec -1 , with the same implantation ion Pt and the same implantation dose of 2.5×10 17 ions·cm -2 Next, MoS 2 The performance of MoS as a carrier is better than that of graphene as a carrier. The main reasons are: graphene can provide good conductivity, but graphene is catalytically inert. 2 The sulfur atom vacancies and edges can play a good catalytic role. Although defect sites are also introduced to anchor Pt single atoms during the injection process, the defects generated are not conducive to MoS 2 It can also enhance its catalytic activity.
[0147] The LSV, Tafel, EIS, and C dl The curves are Figures 17-20 As shown. Figures 17-20It can be seen that the values of Tafel slope are: Example 5 (NF-1mgCNT-3E16Pt) is 69.63mV dec -1 , Example 6 (NF-1mgCNT-3E16Mo) is 35.86mV dec -1 , C dl The values are: Example 5 (NF-1mgCNT-3E16Pt) is 460.9mF / cm 2
[0148] Example 6 (NF-1mgCNT-3E16Mo) is 296.87mF / cm 2 , ions were injected into nickel foam coated with 1 mg CNTs. Mo ions achieved the optimal catalytic effect with their minimum dosage. At the same time, its lowest Tafel slope also confirmed its faster reaction kinetics than commercial Pt / C. Ni-Mo alloy promotes HER reaction, and the electron cloud density of the metal bond formed by the electronic structure of the two is conducive to the adsorption and desorption of hydrogen ions.
[0149] LSV, Tafel, EIS, C dl The curves are Figures 21 to 24 As shown. Figures 21 to 24 It can be seen that the values of Tafel slope are: Example 7 (NF-1mgCNT-1E17Fe) is 56.45mV dec -1 , Example 8 (NF-1mgCNT-1E17Mo) is 80.21mV dec -1 , Example 9 (NF-1mgCNT-2.5E17Fe) is 46.57mV dec -1 , C dl The values are: Example 7 (NF-1mgCNT-1E17Fe) is 137.5mF / cm 2 , Example 8 (NF-1mgCNT-1E17Mo) is 157.93mF / cm 2 , Example 9 (NF-1mgCNT-2.5E17Fe) is 264.33mF / cm 2 , inject 2.5×10 17 ions·cm -2 The Fe ions have the greatest promoting effect on the OER reaction, and the Ni-Fe alloy promotes the OER reaction. -2 The overpotential at is 254 mV, which is better than that of RuO 2(270 mV). In addition, its smallest Tafel slope reflects its fastest reaction kinetics, its smallest EIS radius reflects its smallest charge transfer resistance, and its largest double-layer capacitance value reflects the largest electrochemical active area, representing the largest number of active sites.
[0150] Fig.25 The target plate is used to place the current collector in the process chamber of the ion implanter for ion implantation. Fig.25 It can be seen from the above that the method provided by the present invention can be used for large-scale production.
[0151] In summary, the catalyst prepared by the present invention still has excellent catalytic performance when the catalyst loading is low, and has strong scalability in the selection of current collectors, carriers and injected ion types, and is a very universal catalyst synthesis loading method.
[0152] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for ion implantation to load a catalyst, comprising the following steps: Metal ion implantation is performed on the surface of the current collector to obtain a catalyst; Alternatively: (1) mixing a carrier material with a solvent and a binder to obtain a mixed slurry; the carrier material comprises at least one of graphene, metal chalcogenide, carbon nanotube and graphyne; (2) coating the mixed slurry obtained in step (1) onto a current collector to obtain a current collector loaded with a carrier material; (3) Metal ion implantation is performed on the surface of the current collector of the carrier material obtained in step (2) to obtain a catalyst.
2. The method according to claim 1, characterized in that In the step (1), the ratio of the mass of the carrier material, the volume of the solvent and the volume of the binder is 1 mg: (180-220) μL: (10-20) μL.
3. The method according to claim 1, characterized in that The ratio of the mass of the carrier material in the current collector loaded with the carrier material in step (2) to the surface area of the current collector is (0.5-1.5) mg: 1 cm 2 .
4. The method according to claim 1, characterized in that: The current collector in step (2) comprises one of carbon paper, carbon cloth, foam copper and foam nickel.
5. The method according to claim 1, characterized in that The metal ions in step (3) include at least one of iron ions, cobalt ions, nickel ions, copper ions, gold ions, molybdenum ions, platinum ions, ruthenium ions, aluminum ions, niobium ions, rhodium ions, iridium ions, palladium ions, silver ions, titanium ions, zinc ions, chromium ions and manganese ions.
6. The method according to claim 1, characterized in that The implantation dose of metal ions in step (3) is 1×10 15 ~5×10 17 ions·cm -2 .
7. The method according to claim 1, characterized in that The energy of the low-energy ion beam during metal ion implantation in step (3) is 5 to 100 keV.
8. The method according to claim 1, characterized in that: The metal ion implantation in step (3) is performed under vacuum conditions.
9. The catalyst prepared by the method for loading catalyst by ion implantation according to any one of claims 1 to 8.
10. Use of the catalyst according to claim 9 in producing hydrogen by electrolysis of water.
Citation Information
Patent Citations
Method for preparing catalytic nanoparticles, catalyst surfaces, and / or catalysts
CN112567066A
Method for preparing electro-catalytic material through ion implantation and related application
CN113976121A
High-rate three-dimensional porous silicon-niobium-based oxide composite film negative electrode material and preparation method thereof
CN115207297A
Supported metallic catalyst and manufacturing method thereof
US5525568A